Munich Social Science Review New Series, Volume 2/2019 - Airaksinen, Timo (Verlag Dr. Manfred J. Holler, 2019)
This is the second volume of Munich Social Science Review, New Series. It is devoted to the study of classical and neoclassical economics, public choice, law and economics, psychology and philosophical aspects
Keywords: Law and Economics; Classical Political Economy; Conspiracy Theories